(untitled)
Nowadays, society is characterized by complex systems, in which technology, ease of accessing information and even the increasing use of social networks have given way to new ideologies and subcultures; some of positivist line with univocal tendency and other postmodern, relativistic line, typical of equivocal hermeneutics, that make essential the generation of a critical and proactive conscience, that makes possible what in the words of the Dominican Mauricio Beuchot, is the existence of a hierarchy of approaches to a delimited or delimitable truth. In this sense, it is necessary to recognize the close relationship that exists between education and philosophy to develop, during the educational process, the strengthening of philosophical thinking that favors an educational praxis cohesive with the social fabric, without having the conception of "the modern world is that of simulacra" , which, as Deleuze proposed with the principle of connection and heterogeneity, "any point can be connected to another, and it must be" ; that is, theory and practice cannot be separated from one another, they must always attend to and respond to a reality. Reality and its everydayness require reﬂection, because we cannot be indifferent to it, while also compelling an action, typical of the natural attitude of the human being, to question and try to answer their questions; as Aristotle put it, "all men naturally want to know.